"Kerk" en "volk" uit die hoek van moderne samelewingsteologieë - Labuschagne, J. P. (Hervormde teologiese studies, 1991)
‘Church’ and ‘nation’ from the viewpoint of modem social theologies The essay reflects on the possibilities for meaningful communication, on the themes of church and nation, between the viewpoint of modern social theologies on the one hand and that of Christians who emphasise the value of the identity of the nation ('Volk') on the other.